Pass-Through of Imported Input Prices to Domestic Producer Prices : Evidence from Sector-Level Data - Ahn, JaeBin (IMF Working Papers; Working Paper, 2016)
Motivated by stylized facts pointing to a dominant role of imported inputs in transmitting external price shocks to domestic prices, this paper zooms in to study the pass-through of imported input costs to domestic producer prices. Our approach constructs effective input price indices from sector-level price data combined with sector-level information on input-output linkages. Applying an error correction model specification to sector-level output and input prices, the long-run pass-through rate of effective imported input costs to domestic producer prices is estimated to be around 70 percent in Korea and almost 100 percent in selected European countries.